Perubahan Komposisi Kimia Kulit Buah Kakao Akibat Penambahan Mangan dan Kalsium dalam Biokonversi dengan Kapang Phanerochaete chrysosporium - Suparjo Suparjo; K G Wiryawan; E B Laconi; D Mangunwidjaja (Media Peternakan, 2009)
Bioconversion is a method to increase quality of high lignocellulose-containing feedstuffs. Fermentation occurs during bioconversion is influenced primarily by length of fermentation and mineral supplementation to the medium. This study was aimed at determining the effect of these two factors on dry matter (DM), organic matter (OM), neutral detergent fiber (NDF) and acid detergent fiber (ADF), and cellulose-to-lignin ratio of cocoa pod incubated with Phanerochaete chrysosporium. Twenty four treatments containing of 4 mineral supplementations (no mineral, Ca, Mn, and Ca+Mn) and 6 different lengths of fermentation (0, 5, 10, 15, 20, and 25 days) were designed randomly to 72 fermentation glass jars in a 4x6 factorial arrangement. Length of fermentation had significant effect on all parameters measured. Mineral significantly affected changes of DM and OM, NDF and ADF content, and cellulose-to-lignin ratio, but not DM and OM content. In conclusion, supplementation of Ca to cocoa pod incubated with P. chrysosporium for 15 days contributed positively (P < 0.05) to changes of OM (13.83%) and DM (11.30%). The cellulose-to-lignin ratio of 1.34 was the optimum result of Mn supplementation for 10 days incubation. Key words: Phanerochaete chrysosporium, cocoa pod, fermentation, mineral supplemention, fiber